An ornithological survey of Gunung Mulu National Park, Sarawak, Malaysian Borneo - Burner, R.C.; Chua, V.L.; Brady, M.L.; Van, Els P.; Steinhoff, P.O.M.; Rahman, M.A.; Sheldon, F.H. (Wilson Ornithological Society, 2016)
Mount Mulu, an isolated 2,376 m peak in eastern Sarawak, Malaysian Borneo, has not been thoroughly surveyed for bird species since shortly after the creation of Mount Mulu National Park in 1974. The Park is of particular interest for its isolation, spectacular limestone structures, bat flights, and extensive primary forest that ranges from near sea level to the mountain's peak. We spent 2.5 months surveying, observing, and mist-netting birds in the Park and recorded 244 species across its elevational gradient from 50-1,850 m, including 32 species new to the 1979-82 Mt. Mulu checklists. Here, we report the elevational range of each species we observed, compare our list with these earlier Mt. Mulu checklists compiled 25 years ago, and comment on unique observations.